Building STAIS Student Character Through The Program (Kdbm) In The Philosophical Perspective Of Constructivism - Faelasup (CV. Kalimasada Group Profesional, 2023)
KDBM activities are very strategic activities as a means of learning for students, because in the program they combine theory and action. Departing from a fundamental question, how the KDBM program can build the character of STAIS students in the perspective of constructivist philosophy. This research is a qualitative research, the type of field research is the method used, observation, documentation and interviews. The results of this study indicate that KDBM activities in the perspective of constructivism can foster cognitive awareness, spiritual awareness, and social sensitivity or social piety. Then KDBM activities have also formed four feelings in the personality of the students, namely: First, heart training, second, mental exercise, Third, thinking, fourth, sports. The series of three awareness and four senses is a concrete result of the KDBM activities in the perspective of constructivism.